Guidance Law with Desired Impact Time and FOV Constrained for Antiship Missiles Based on Equivalent Sliding Mode Control - Shuangxi Liu; Binbin Yan; Tong Zhang; Pei Dai; Jie Yan (International Journal of Aerospace Engineering)
Impact time control guidance (ITCG) is an important approach to achieve saturation attack on targets. With the increasing complexity of warfare requirements for missiles, an ITCG with field-of-view (FOV) constrained for antiship missiles is proposed based on equivalent sliding mode control. Firstly, in view of the accuracy of the calculation of remaining impact time for guidance law, the large initial lead angle is taken into consideration in the estimation of remaining flying time in which there is no need for the assumption of small angle approximation. Besides, for the sake of promoting the practical application value of the proposed guidance law, FOV is considered so that it can satisfy the actual working performance of the seeker. Then, combined with the concept of predicted interception point (PIP), the proposed guidance law is applied to attack a moving target. Numerical analysis is carried out for different initial lead angles, various impact time, different methods of estimating remaining flying time, and cooperative attack conditions. Compared with proportion navigation guidance (PNG), the feasibility and effectiveness of the guidance law are verified. Simulation results demonstrate that the proposed guidance law can guarantee the constraints of both impact time and FOV effectively.